ANALISIS PERBEDAAN KINERJA PETANI KAKAO MITRA DAN NON MITRA DENGAN PT OLAM INDONESIA DI KABUPATEN PESAWARAN - Rahmi Eka Putri; Zainal Abidin; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This research intended to differentiate the productivity and cocoa farming revenue of partner farmers and non-partner farmers in in Sungai Langka and Wiyono villages of Pesawaran district.  The research was conducted by survey method in which data was collected in January 2017 and analyzed by descriptive quantitative method.  The locations of this research were chosen by gradual sampling.  This research envolving all 54 cocoa farmers as respondents in that villages.  The data was analyzed by analysis tools of difference and farming revenue.  The results showed that based on the analysis of difference there was no difference in cocoa  productivity between partner farmers and non-partner farmers; whereas, there was difference in cocoa farming revenue between partner farmers and non-partner farmers Key words: cocoa, farmers, non-partner, partner